2010
DOI: 10.2746/042516405775314853
|View full text |Cite
|
Sign up to set email alerts
|

Use of serum amyloid A and other acute phase reactants to monitor the inflammatory response after castration in horses: a field study

Abstract: Measurements of SAA and iron may improve post operative monitoring. As sustained inflammation may indicate that the surgical wound has become infected, SAA and iron measurements may facilitate early recognition and hence early treatment of infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

23
101
4
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 99 publications
(133 citation statements)
references
References 16 publications
23
101
4
5
Order By: Relevance
“…The postsurgical inflammatory and infectious complications are also accompanied by significantly higher values of SAA [31], that correlate with the severity of symptoms. Thus, monitoring the SAA allows making quick decisions about the treatment to apply, and thus decrease the discomfort and postoperative complications [22,29].…”
Section: Surgerymentioning
confidence: 92%
See 4 more Smart Citations
“…The postsurgical inflammatory and infectious complications are also accompanied by significantly higher values of SAA [31], that correlate with the severity of symptoms. Thus, monitoring the SAA allows making quick decisions about the treatment to apply, and thus decrease the discomfort and postoperative complications [22,29].…”
Section: Surgerymentioning
confidence: 92%
“…Some studies have suggested that SAA is even more sensitive than classical markers of inflammation, such as white blood cell count and Fb [30,31], as stated previously. Various factors such as fear, excitement and infections, among others, mainly induce increased cortisol and neutrophilic leukocytosis type levels.…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations